WIDEBAND TELECOMMUNICATION CHANNEL WITH ADAPTIVE ANTENNA ARRAYS WITH INCOMPLETE SIGNAL STRUCTURE KNOWLEDGE IN MULTIPATH PROPAGATION - Pliushch, Oleksandr; Savchenko, Alina (Science-based technologies, 2022)
The paper deals with research into performance of а wideband telecommunication channel with direct spectrum spreading in multipath signal propagation with deployment of adaptive antenna arrays that function according to root mean square error criterion. It is stressed that for root mean square criterion implementation in adaptive arrays, substantial challenge in practical realization is reference signal formation. It is proposed to use for deriving the reference signals wideband signals with direct spectrum spreading that are formed with the help of pseudo noise coding sequences. In using such signals, it is envisioned to deploy RAKE receiver to determine multipath components delays and, in such a way, to obtain reference signals for root mean square criterion. It is stressed that the real wideband signal comprises at least two pseudo noise coding sequences, which spread and scramble the spectrum, and the bit sequence, which transmits the desired signal. Computer simulation of a wideband telecommunication channel is carried out in the conditions of total knowledge of all three components of the wideband signal, two components and only one of them. Computer simulation results allows one to come to the conclusion that lack of knowledge about wideband signal components leads to substantial performance deterioration of adaptive antenna arrays due to impossibility to form the exact reference signal. It is proposed to deploy two approaches to securing adaptive antenna arrays operation in the conditions of incomplete knowledge about the structure of the wideband signal being transmitted in the channel. The first one envisions using discontinued adjustment of adaptive antenna arrays only in the periods of the frame sync pulse transmission, which for the scrambling sequence and the bit sequence of the desired signal always equals unity. The other approach concerns adaptation only in the time intervals with the training sequence transmission, which is known beforehand. It is proposed to carry out further research on studying adaptive performance of adaptive antenna arrays in the discontinuous mode of their adjustment.